Enhancement process of AES: a lightweight cryptography algorithm-AES for constrained devices - Hussein M. Mohammad; Alharith A. Abdullah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
The restricted devices have a small memory, simple processor, and limited power. To secure them, we need lightweight cryptography algorithms, taking into account the limited specifications. Lightweight cryptography (LWC) algorithms provide confidentiality and maintain information integrity for devices with limited resources. This paper improves and enhances advanced encryption standard (AES) algorithm by reducing algorithm computation power and improving cryptography performance from the point of resource constraint devices. The proposed algorithm is fast and lightweight, which is essential for securing all kinds of data. Besides, the use of mix column overhead is dispensing with, and the ciphertext is processed by the mathematical function (continued fraction) to compress the ciphertext and make it more confusing and also to increasing the data transfer speed. The proposed lightweight cryptography-AES (LWC-AES) algorithm highly suitable for the timely execution of encryption and decryption (such as when encrypt text has (45.1 KB) encryption execution time for AES was (294 ms), while in LWC-AES was (280 ms), as well as suitable for the memory size of the resource-constrained devices for all types of data, than the AES algorithm. The proposed algorithm tested for security analysis using the Avalanche Effect parameter, and this test showed acceptable and within required security results